Pemahaman Konsep Matematis Siswa Kelas 10 ditinjau dari Kemandirian Belajar pada Materi Perpangkatan - Anisah Anisah; Suhartati Suhartati; Bintang Zaura (Universitas Syiah Kuala, 2023)
Conceptual understanding is a fundamental skill that students must acquire, making it a key objective in mathematics education. However, there is room for improvement in students' comprehension of mathematical concepts in schools. One psychological aspect that can enhance students' success in learning mathematics is their learning independence. This study explores the relationship between students' understanding of mathematical concepts and their level of learning independence, specifically in the topic of powers. The research employed a qualitative approach with a descriptive design, involving 30 10th-grade students as participants. Data was collected through independent learning questionnaires, tests assessing understanding of mathematical concepts, and interviews. The study's findings reveal that students' understanding of mathematical concepts varies according to their level of learning independence. Students with high learning independence demonstrate a firm grasp of concepts, falling within the high category and fulfilling all six indicators of understanding mathematical concepts. Those with a moderate level of independence display a solid understanding, falling within the medium category and fulfilling five indicators. In contrast, students with low learning independence exhibit a limited understanding, falling within the low category and fulfilling only one indicator of understanding mathematical concepts.